Seasonal Variation in Rice Price Transmission in Indonesia - Zhena Nofhatiaz Zahra; Zikra Fernando; Rio Akbar Rahmatullah (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Rice is a strategic commodity serving as the staple food in Indonesia. Price transmission in the rice supply chain is critical for market efficiency and food security, yet existing studies often overlook seasonal variations and nonlinearity. This study aims to analyze seasonal variations in rice price transmission across producer, wholesaler, and traditional market levels in Indonesia during different seasons (February-May, June-September, October-January). The study employs monthly time-series data on medium rice prices from February 2020 to February 2025. The Nonlinear Autoregressive Distributed Lag model is used to capture short and long-run price transmission. Stationarity, cointegration, and Wald tests are conducted to validate the model. The findings reveal significant asymmetric price transmission during February-May and June-September, with farmers more vulnerable to price declines. Meanwhile, wholesalers and traditional markets responding faster to price increases. The October-January period shows stagnant dynamics due to low market activity. Long-run asymmetry is prevalent, indicating persistent market inefficiencies. Seasonal variations significantly influence rice price transmission in Indonesia, highlighting the need for season-based policy interventions to stabilize prices and protect farmers. Enhancing farmers' bargaining power and implementing technology-driven price monitoring systems are recommended to mitigate asymmetry and improve market efficiency